Surgical fixation of hip fractures– a novel technique for pre-operative planning - Zi Qiang Glen Liau; Kamaraj Thirukumaran; Seth Ian Sim; Alexander Shao-Rong Pang (Journal of Orthopaedic Surgery and Research)
Abstract Purpose The dynamic hip screw (DHS) is a widely used method for hip fracture stabilisation, but conventional DHS (CHDS) fixations may be limited by longer surgical duration and delayed recovery compared to minimally invasive DHS (MIDHS) fixations. We describe a novel low-cost surgical method that reduces intraoperative time, peri-operative complications, and improves overall patient outcomes. Methods A prospective double-blinded study included 15 patients who underwent surgical fixation of IT hip fractures using a 4-hole DHS system. All surgeries were performed at a tertiary referral hospital between January 2019 and April 2023 by surgeons with similar levels of experience. Main outcome measurements included tip-apex distance (TAD), surgery duration, haemoglobin loss, and hospital stay duration. Two independent assessors measured TAD using the post-operative anteroposterior and lateral radiographs. Kyle’s classification was used to categorize the IT fractures. IBM SPSS Statistics 26.0 for Mac (SPSS, Chicago, IL, USA) was used for the statistical analysis. Statistically significant difference was defined as p-value < 0.05. Results Both groups had similar baseline characteristics (p > 0.05). Both groups had similar complexity in fractures, but the mean surgical duration was significantly shorter (p = 0.019) (43.8 ± 12.3 min) compared to the CDHS group (73.4 ± 18.2 min). Postoperatively, there was no significant difference (p > 0.05) in hospital stay duration, haemoglobin (Hb) loss, or TAD. Conclusions MIDHS group had shorter surgical duration compared to CDHS group, with no significant difference in TAD, haemoglobin loss and hospital stay duration.